The Guiding Role of Christian Faith in John C.H. WU’s Legal Thought - KANG , Xiaorong (Journal of Research for Christianity in China (JRCC), 2025)
This paper focuses on John C. H. Wu’s legal philosophy, profoundly influenced by Christian faith, aiming to gain insight into the broader picture through a specific example.